The role of face masks on speech intelligibility for native and nonnative speakers of English: Graduate students’ experiences - Guskaroska, Agata (Journal of Academic Language and Learning, 2021)
The COVID-19 pandemic caused the widespread use of face masks in teaching and other normal communication situations. To provide some insight into the communication issues the wearing of face masks causes, this qualitative study examined beliefs about the role of face masks on speech intelligibility by exploring graduate students’ experiences. Data was collected by interviewing eight native speakers and eight non-native speakers of English in a large Midwestern university in the U.S.A. in December, 2020 while the COVID-19 pandemic was still ongoing. Data was analyzed by using a phenomenology approach and themes were identified. Findings indicated that both native speakers and nonnative speakers view speech with face masks as some kind of obstacle to speech intelligibility, either as speakers or as listeners, pointing towards various factors that cause the difficulty. It was also found that speakers tend to use various strategies to adapt their speech when wearing face masks to facilitate the communication. Frameworks of the factors and strategies are presented. The findings of this study can provide implications for anyone involved in academic, medical, or occupational settings, as well as for the general public during pandemic situations.